A dimensão socioambiental nos planos diretores dos municípios lindeiros ao lago de Itaipu - Brasil - Grosseli, Sirlei (2022)
The historical review of the urbanization process demonstrates that the disorderly growth of cities aggravates socio-environmental problems. The Federal Constitution and the City Statute regulated urban policy, instituting the Master Plan (MP) as the basic instrument in the planning of socially fairer and more sustainable cities, giving it urban instruments that help control real estate speculation and protect the environment. The Law also determines that the MPs must be reviewed at least every ten years, so that they are kept up to date with the changes that arise in cities over time. The municipalities bordering Itaipu hydroelectric power plant lake had part of their land flooded, resulting in permanent impacts, with socio-environmental damage. Thus, the present dissertation focused on verifying how the socio-environmental dimension is present in the MPs of these municipalities. In this way, the research sought to identify and quantify the number of objectives and strategies within the municipal themes of the Master Plans, with the intention of analyzing the importance that each MP dedicated to the socio-environmental themes of housing, environment, sanitation and mobility/traffic. The identification, in the MP, of the presence of urban instruments, established by the City Statute, to enforce the socio-environmental function of the property, also helped to answer the research problem. As a result, it was identified that, of the 16 neighboring municipalities, one still did not have a Master Plan and of the 15 that did, 8 have not reviewed the laws for more than 10 years. Regarding the socio-environmental aspect of the analyzed municipalities, IBGE data indicated that human development in the region is below average, as 12 of the 16 neighboring municipalities had an HDI below the average of their states. The rates of households with adequate sanitation and streets with equipment, such as culverts and sidewalks, also indicated deficiencies in the areas of sanitation and mobility/traffic. The analysis of the number of objectives and strategies in the themes of Housing, Sanitation, Environment and Mobility/Transit showed that the first three had greater relevance in most municipalities. The Mobility/Transit theme did not receive significant numbers of objectives and strategies in most Master Plans, demonstrating that in smaller municipalities there is a lack of knowledge on the subject, since data on infrastructure of the roads showed deficiencies that need to be remedied. Data analysis indicated points where the MPs require more attention in future revisions. As for the use of urban planning instruments, the results showed that most municipalities cite all the instruments selected in the research. Only one municipality did not make maps with the areas of the Special Areas of Social Interest and conservation units available on the institutional portals, which compromises the transparency and effectiveness in the use of these tools.